In Vitro Activity of Essential Oils from Piper Species (Piperaceae) against Tachyzoites of Toxoplasma gondii - Adalberto Alves Pereira Filho; Mariana Maciel Cunha; Mariana Alves Stanton; Lydia Fumiko Yamaguchi; Massuo Jorge Kato; Érica S. Martins-Duarte (Metabolites, 2023)
Toxoplasmosis is a tropical and neglected disease caused by the parasitic protozoa Toxplasma gondii. Conventional treatment with sulfadiazine and pyrimethamine plus folinic acid, has some drawbacks, such as inefficacy in the chronic phase, toxic side effects, and potential cases of resistance have been observed. In this study, the activity of essential oils (EOs) from three Piper species and their main constituents, including α-Pinene (Piper lindbergii and P. cernuum), β-Pinene (P. cernuum), and dillapiole (P. aduncum), were evaluated against tachyzoites of T. gondii. α-Pinene was more active [(IC50 0.3265 (0.2958 to 0.3604) μg/mL)] against tachyzoites than P. lindbergii EO [0.8387 (0.6492 to 1.084) μg/mL]. Both α-Pinene and P. lindbergii EO exhibited low cytotoxicity against NHDF cells, with CC50 41.37 (37.64 to 45.09) µg/mL and 83.80 (75.42 to 91.34) µg/mL, respectively, suggesting they could be of potential use against toxoplasmosis.